Perception of treatment burden, psychological distress, and fatigue in thyroid cancer patients and their partners – effects of gender, role, and time since diagnosis. Issue 2 (15th July 2015) - Drabe, Natalie; Steinert, Hans; Moergeli, Hanspeter; Weidt, Steffi; Strobel, Klaus; Jenewein, Josef
Abstract: Objectives: The aim of this study was to examine diagnosis and treatment burden as well as psychological distress (anxiety and depression) and fatigue in thyroid cancer patients and their partners, focusing on the effects of gender, role, and time since diagnosis. Methods: Seventy‐one patients diagnosed and treated for differentiated thyroid cancer within the past 7 years, participated in this online study, as well as 40 partners. Standardized questionnaires were used rating anxiety, depression, fatigue, and quality of life. Suffering in the context of diagnosis and treatment was evaluated using numeric analog scales. Patients' most recent hormone status was integrated into analysis. Results: Male and female patients but not their partners had significantly higher mean anxiety scores ( p  < 0.001) than the norm. Severe fatigue that warrants observation and treatment was reported by two of 21 male patients (9.5%), 12 of 50 female patients (24%), two of 28 male partners (7.1%), and no female partners. With respect to diagnosis and treatment burden, female partners expressed the highest burden, while male patients expressed the lowest. This burden was associated with current fatigue levels in male patients and with current anxiety, depression, and fatigue levels in female patients. Conclusions: Although both patients and partners suffer from the diagnosis and treatment of differentiated thyroid cancer, only patients are at risk of developing anxiety symptoms or fatigue. A simple question like 'How did being told you have thyroid cancer affect you?' might successfully screen for patients who are at risk. Copyright © 2015 John Wiley & Sons, Ltd.